The Lysenko Controversy as a Global Phenomenon, Volume 1
XIV, 191 p. 10 illus., 8 illus. in color.
Keywords: This volume covers the global history of the Lysenko controversy, while exploring in greater depth the background of D. Lysenko’s career and influence in the USSR. By presenting the rise and fall of T.D. Lysenko in a variety of aspects—his influence upon art, unrecognized predecessors, and the extent to which genetics continued in the USSR even while he was in power, and the revival of his reputation today—the authors provide a fresh perspective on one of the most notorious episodes in the history of science.